Burst of intracloud current pulses during the initial continuous current in a rocket‐triggered lightning flash. Issue 24 (23rd December 2014) - Lu, Gaopeng; Jiang, Rubin; Qie, Xiushu; Zhang, Hongbo; Sun, Zhuling; Liu, Mingyuan; Wang, Zhichao; Liu, Kun
Abstract For a rocket‐triggered lightning flash on 2 August 2013, the measurement with one pair of broadband low‐frequency (20–400 kHz) magnetic induction coils registered a long sequence of over 600 intermittent pulses during the initial continuous current. The timescale of these pulses is about 3‐8 µs, and the typical interpulse interval is about 30 µs. The source discharges of these pulses, which are not readily detectable in the frequency range (140–300 MHz) of a short‐baseline very high frequency (VHF) lightning imaging system, are attributed to the stepping processes when the positive leader propagated into the cloud region. The reversals in the polarity of magnetic pulses are related to the variation in the vertical direction of positive leader propagation as resolved by the VHF imaging system.